O Procedimento das Casinhas do Projeto Alfaletrar como estratégia para a gradação das relações grafemas e fonemas: uma experiência de intervenção didática do PIBID - Cassote, Leila Camila Pereira Lisboa (Brasil, 2025)
Every child has the right to be literate and literate in the social practices of language and writing, as advocated by author Magda Soares. In 2020, with the outbreak of the Covid-19 pandemic, reading and writing teaching was mainly compromised to students from public schools. In order to ensure a significant literacy and literacy, the Institutional Program of Scholarships for Teaching-PIBID of the Faculty of Education of the Federal University of Amazonas has developed Intervention Projects that assist in the pedagogical practices of teachers from the initial years of elementary school of the municipal public network. For this, training meetings and planning were held that prepared the scholarship students for the practices in the school research field. Subsequently, an intervention action was developed replicating with adaptations the Procedure of the Houses of the Alfaletrar Project in Lagoa Santa-MG, as a strategy for the appropriation of the grapheme and phoneme relations with students of the 1st, 2nd and 3rd year of Elementary School in the literacy phase. This experience was the result of a combination of bibliographical research, creation of activities adapted from the Alfaletrar Project and the theoretical foundations of Heloísa Vilas Boas. It was proven that it is possible to obtain advances in the reading and writing hypotheses described in the theory of Psychogenesis of the Written Language by Emília Ferreiro and Ana Teberosky, provided that the teacher understands the students' needs and works with the use of texts, phrases and words, valuing the social and cultural context and previous knowledge of the students attended.